Analisis Yuridis Proses Peradilan Tindak Pidana Korupsi di Pengadilan Negeri Kelas IA Palembang - Indra Ade Kurniawan (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
The Corruption Court in the Class IA Palembang District Court in examining corruption cases uses the procedural law used in examinations at the corruption court, namely Law Number 8 of 1981 concerning the Criminal Procedure Code, equipped with certain articles. The method used in this study is a qualitative method with a literature approach. The results of the study state that there are obstacles faced by the Class IA Palembang District Court in resolving the Corruption Crime, namely obstacles that arise from the law itself, in addition to constraints from Law Enforcement Officials, constraints on facilities or facilities, constraints on community environmental factors, and constraints arising from the perpetrator himself.